Data from: Evolutionary patterns in the geographic range size of Atlantic Forest plants - Leão, Tarciso; Nic Lughadha, Eimear; Reich, Peter (Dryad, 2020)
Species’ geographic range size is arguably the single most important
predictor of vulnerability to extinction and a key metric in ecology.
Despite this, patterns of specific variation in range size and their
underlying reasons are still poorly understood. For example, hypotheses on
how evolutionary history affects range size have scarcely been tested. To
address these questions, we focused on Brazil’s Atlantic Forest flora, one
of the most species-rich in the world, relatively well-known and highly
threatened. We investigated whether and how lineages’ diversification
rate, number of species and age are associated with species’ geographic
range size. We estimated the extent of occurrence and area of occupancy of
each of 13,283 plant species native to the Atlantic Forest region based on
over 500,000 unique records. We used phylogenetic least squares and
logistic regressions to analyze how the predictors affect the geographic
range size. On average, the higher the diversification rate and number of
species in the lineage, the smaller the species range size and the higher
the proportion of species with vulnerably small range size. Lineage age
showed no clear effect on average range size. The results support our
expectations that dynamics of diversification and taxonomic richness
considerably affect the species range size. Finally, this work reveals
poorly known patterns of range size variation and some of the mechanisms
driving variation in range size and vulnerability to extinction.
Keywords: diversification rate; evolutionary age; vulnerability to extinction